2009
DOI: 10.1371/journal.pcbi.1000491
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of Lactase Persistence in Europe

Abstract: Lactase persistence (LP) is common among people of European ancestry, but with the exception of some African, Middle Eastern and southern Asian groups, is rare or absent elsewhere in the world. Lactase gene haplotype conservation around a polymorphism strongly associated with LP in Europeans (−13,910 C/T) indicates that the derived allele is recent in origin and has been subject to strong positive selection. Furthermore, ancient DNA work has shown that the −13,910*T (derived) allele was very rare or absent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
381
0
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(403 citation statements)
references
References 56 publications
11
381
0
11
Order By: Relevance
“…1 Although this distribution would suggest an origin of the mutation in the populations living in the North, a recent modelling of the evolutionary history of the mutation has rather surprisingly suggested its origin in a region located between the Central Balkans and Central Europe, which spread through the dissemination of Neolithic Linearbandkeramiek culture. 36 Although this may seem counterintuitive on the first sight, other simulations have also shown that the geographic origin of an allele can differ from the region of highest frequency, in particular when it occurs on the wave front of a demographic expansion. 37,38 On the basis of these data, one may speculate regarding the likely arrival of the lactase persistence genotype with Neolithic farmers arriving around 7000 YBP from Central Europe.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although this distribution would suggest an origin of the mutation in the populations living in the North, a recent modelling of the evolutionary history of the mutation has rather surprisingly suggested its origin in a region located between the Central Balkans and Central Europe, which spread through the dissemination of Neolithic Linearbandkeramiek culture. 36 Although this may seem counterintuitive on the first sight, other simulations have also shown that the geographic origin of an allele can differ from the region of highest frequency, in particular when it occurs on the wave front of a demographic expansion. 37,38 On the basis of these data, one may speculate regarding the likely arrival of the lactase persistence genotype with Neolithic farmers arriving around 7000 YBP from Central Europe.…”
Section: Discussionmentioning
confidence: 99%
“…51 However, computer simulations have shown that its increased frequency particularly in North Europe does not necessarily imply stronger effect of positive selection there than in other parts of Europe. 52 Ancient DNA evidence for the Y-chromosome M458G allele is still lacking and it is therefore possible only to speculate about its existence and prevalence in Neolithic Europe. Beyond its spread in the Central European river basins (Figure 2), the LBK extended around the northern Carpathians into the steppe zone of Ukraine and participated in the establishment of the Crisç ulture.…”
Section: Phylogeographymentioning
confidence: 99%
“…Thomas and his colleagues estimated the timing by looking at genetic variations in modern populations and running computer simulations of how the related genetic mutation might have spread through ancient populations 4 . They proposed that the trait of lactase persistence, dubbed the LP allele, emerged about 7,500 years ago in the broad, fertile plains of Hungary.…”
Section: Strong Stomachsmentioning
confidence: 99%